Study the Effects of Anadrol Overdose on Liver Function in Male Rats - Qassim A Zigam; Zahraa Sami Mohammed; Ahmed Obaid Hossain (College of Pharmacy University of Baghdad, 2022)
Anadrol (oxymetholone) is an active androgenic anabolic steroid that has been clinically studied in numerous diseases since the 1960s. It is used in the treatment of anemia and the replacement of male sex steroids. Unfortunately, in attempts to improve physical performance, Anadrol could be misused by athletes, that can lead to poisoning contributes to hepatotoxicity. The aim of this study was to investigate the impact of anadrol on the liver function in rat model, via assessment of liver enzymes and histopathological study. A forty male rats, weights about (200-300 gm), aged 8-12 weeks, after acclimatization, the rats were ‎randomly divided into four groups (10 rats in each group) as follow: control group (in which all rats were administered normal saline (NS) via oral gavage), anadrol 10 mg/kg (Iran-Tehran Company) group (in which all rats were administered  anadrol 10mg/kg via oral gavage), anadrol 20 mg/kg group (in which all rats were administered anadrol 20mg/kg via oral gavage), and anadrol 30 mg/kg group (in which all rats were administered anadrol 30mg/kg via oral gavage), the oral administration had continued for 8 weeks in single daily dose regimen. At the end of study liver function enzymes such as alanine aminotransferase & aspartate aminotransferase were measured via chemical analysis. Then histopathological study was done on the liver tissue in the four experimental groups. Male rats that treated with anadrol displayed high level of liver enzymes, including as alanine aminotransferase & aspartate aminotransferase, as compared with control group. On the other hand, histopathological study exhibited significant injurious changes in the hepatic tissue in anadrol groups comparing with control. When anadrol given in high doses results in hepatic injury, that can be cleared via elevated levels of hepatic enzymes and liver histopathological changes.